PATTERN OF CLINICAL MANIFESTATION OF HIV IN PATIENTS OF TUBERCULOSIS DIAGNOSED BY DIFFERENT DIAGNOSTIC MODALITIES - ASHISH KOSHTI; ARCHANA SHRIVASTAVA; NEELKAMAL KAPOOR (International Journal of Pharma and Bio Sciences, 2013)
In developing countries, TB is one of the most common opportunistic infections in people who are seropositive for HIV-1. The risk of developing tuberculosis (TB) is estimated to be between 20-37 times greater in people living with HIV than among those without HIV infection. In 2009, there were 9.4 million new cases of TB, of which 1.2 (13%) million were among people living with HIV. With a high prevalence of TB infection in India, the problem of TB related to HIV infection also poses a major public health challenge, particularly in the high HIV burden States. The exact magnitude of HIV among TB patients is unknown as routine surveillance of HIV among TB patients is not undertaken. HIV screening has been done in 129 patients of tuberculosis diagnosed by chest x-ray, sputum AFB, FNAC lymphnode and histopathological examination. Out of them , 17 cases were reactive for HIV. Among Sputam positive cases of AFB, 4(8.1%) were seropositive for HIV. Cough, chest pain, diarrhoea and oral thrush were commonest clinical manifestation. This study shows a pattern of clinical manifestation of HIV and tuberculosis.